Citizens in Hyperconnection: How to Civic Engagement Building through Character Education on Digital Platforms? - Anggraeni, Leni; Wahyudin, Dinn; Azis, Abdul; Baeihaqi, Baeihaqi; Putra, Tarekh Febriana; Wadu, Ludovikus Bomans (Jurnal Moral Kemasyarakatan, 2024)
This study aims to investigate how to build civic engagement through character education on digital platforms. This research explores the influence of citizen attitudes and behaviors on digital platforms on the development of the characters of citizen awareness, participation and commitment. The method used is a quantitative approach. Data collection was conducted through a field survey using a validated and reliable questionnaire, designed according to quantitative research standards. The target population of this study were undergraduate students of Universitas Pendidikan Indonesia with a sample of 394 students selected through cluster sampling from 14 faculties, according to the Slovin formula. Data analysis used descriptive statistics, normality, and homogeneity tests. The results showed that in the attitude domain, citizens showed a good level of engagement, but their behavior showed a low level of engagement. Factors such as disinterest in sharing digital content related to character education, lack of skills in creating digital content, and infrequent preference to use social media are the main causes of this disparity. The implications of this study highlight the need for consistency in building commitment to civic action in citizen engagement in the digital era.